2008
DOI: 10.1097/meg.0b013e3282fc7390
|View full text |Cite
|
Sign up to set email alerts
|

Role of host and bacterial virulence factors in Escherichia coli spontaneous bacterial peritonitis

Abstract: Fluoroquinolone-resistant E. coli spontaneous bacterial peritonitis prevalence is increasing because of norfloxacin prophylaxis. Strains from peritonitis are less virulent than strains from pyelonephritis because of a higher prevalence of A+B1 phylogeny and quinolone resistance. Mortality is related to immunosuppression, but not to bacterial virulence factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…E coli is one of the most frequently isolated bacteria causing SBP, particularly when community-acquired 10 58. The use of β blockers in advanced liver cirrhosis has recently been reported to lower the probability of community-acquired SBP,59 and a recent meta-analysis concluded that this protective effect is even independent of the haemodynamic response achieved 60.…”
Section: Discussionmentioning
confidence: 99%
“…E coli is one of the most frequently isolated bacteria causing SBP, particularly when community-acquired 10 58. The use of β blockers in advanced liver cirrhosis has recently been reported to lower the probability of community-acquired SBP,59 and a recent meta-analysis concluded that this protective effect is even independent of the haemodynamic response achieved 60.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who develop resistance to quinolones, trimethoprim/sulfamethoxazole has been suggested as an alternative to norfloxacin [78] . However, there is a high rate of SBP caused by trimethoprimsulfamethoxazole resistant Gram-negative bacteria (44%-72%), suggesting that this antibiotic is not a suitable alternative to norfloxacin [79,80] . Data supporting the use of trimethoprim/sulfamethoxazole are weak, while its side effects are potentially dangerous and probably under-reported [81] .…”
Section: Secondary Prophylaxis In Patients With Prior Sbpmentioning
confidence: 99%
“…A majority of the studies (15 of 18) were retrospective and 78% (14 of 18) stated relevant baseline data. The accepted definition of SBP was applied in 11 of 18 (61%) of the studies, whereas the rest required culture positivity in addition to an increased neutrophil count, 11,14,15,1820 or based the diagnosis of SBP on hospital diagnostic codes. 10 Three studies evaluated only Escherichia coli -positive SBP.…”
Section: Description Of Prognostic Studiesmentioning
confidence: 99%
“…10 Three studies evaluated only Escherichia coli -positive SBP. 11,18,19 All studies reported the number of deaths but only 50% (9 of 18) stated the causes of death and only 3 studies did not overfit variables. 10,15,20 Ten studies fulfilled our predefined quality criteria.…”
Section: Description Of Prognostic Studiesmentioning
confidence: 99%